Spatial Accuracy of Predictive Saccades Determines the Performance of Continuous Visuomotor Action - Aoyama, Chisa; Goya, Ryoma; Suematsu, Naofumi; Kadota, Koji; Yamamoto, Yuji; Shimegi, Satoshi (Frontiers in Sports and Active Living, 2022)
In a table tennis rally, players perform interceptive actions on a moving ball continuously in a short time, such that the acquisition process of visual information is an important determinant of the performance of the action. However, because it is technically hard to measure gaze movement in a real game, little is known about how gaze behavior is conducted during the continuous visuomotor actions and contributes to the performance. To examine these points, we constructed a novel psychophysical experiment model enabling a continuous visuomotor task without spatial movement of any body parts, including the arm and head, and recorded the movement of the gaze and effector simultaneously at high spatiotemporal resolution. In the task, Gabor patches (target) moved one after another at a constant speed from right to left at random vertical positions on an LC display. Participants hit the target with a cursor moving vertically on the left side of the display by controlling their prehensile force on a force sensor. Participants hit the target with the cursor using a rapid-approaching movement (rapid cursor approach, RCA). Their gaze also showed rapid saccadic approaching movement (saccadic eye approach, SEA), reaching the predicted arrival point of the target earlier than the cursor. The RCA reached in or near the Hit zone in the successful (Hit) trial, but ended up away from it in the unsuccessful (Miss) trial, suggesting the spatial accuracy of the RCA determines the task's success. The SEA in the Hit trial ended nearer the target than the Miss trial. The spatial accuracy of the RCA diminished when the target disappeared 100 ms just after the end of the SEA, suggesting that visual information acquired after the saccade acted as feedback information to correct the cursor movement online for the cursor to reach the target. There was a target speed condition that the target disappearance did not compromise RCA's spatial accuracy, implying the possible RCA correction based on the post-saccadic gaze location information. These experiments clarified that gaze behavior conducted during fast continuous visuomotor actions enables online correction of the ongoing interceptive movement of an effector, improving visuomotor performance.